2019
DOI: 10.1039/c9cp04143e
|View full text |Cite
|
Sign up to set email alerts
|

SnP2S6 monolayer: a promising 2D semiconductor for photocatalytic water splitting

Abstract: Schematics for the exfoliation of the SnP2S6 monolayer from its bulk counterpart and its application in solar driven water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 52 publications
0
21
1
Order By: Relevance
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the previous reports, 46–48 we finally calculate the Gibbs free energy profiles of the OER and HER involved in photocatalytic water splitting on the GaSe and β-SnS surfaces, respectively. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To address the photocatalytic water splitting, the Gibbs free energy profiles of the OER and HER processes on the GaSe and β-SnS surfaces, respectively, are calculated by adopting the method from previous reports, 46–48 see the ESI †…”
Section: Computational Model and Methodsmentioning
confidence: 99%
“…Consequently, triple-layered and four-layered Ge 4 Se 9 structures also have satisfactory edge alignment for water splitting. Although the VBM levels are far from the water oxidation potential, they might be tuned by the strain as reported in the literature. ,, …”
mentioning
confidence: 82%
“…In an early study, g-C 3 N 4 and TiO 2 were demonstrated to be two of the most representative photocatalysts. , Recently, some renowned 2D materials, such as transition-metal dichalcogenides, , metal phosphorus trichalcogenides, , and group III metal mono­chal­co­genides MX (M = Ga, In; X = S, Se), GeX (X = S, Se), and MXene, have been identified as promising photocatalysts for water splitting. Meanwhile, some emerging 2D materials, such as SnN 3 , SiP 2 , MOI (M = Ga, In), pSiX (X = P, As), XP 3 (X = Sb, Ga), PdSe 2 , SnP 2 S 6 , P 4 O 2 , XAs (X = Si, Ge, Sn), and MgX 2 Se 4 (X = Al, Ga), also have been predicted to hold great potential for photocatalytic water splitting as well. In particular, Zhang et al screened over 5000 inorganic compounds from the Materials Project database and successfully proposed 36 candidate 2D structures with validating stability and appropriate band edge positions for water splitting .…”
mentioning
confidence: 99%
“…[15][16][17][18][19][20] Twodimensional materials, such as graphene, MXene and black phosphorus (BP) have unique electronic, thermal, mechanical and photonic properties, which are widely used as functional layers for 2D perovskite photo-electric equipment. [21][22][23][24][25][26][27] Especially, twodimensional transition metal dichalcogenides (TMDs) as the functional layers can signicantly improve the efficiency of 2D inorganic halide perovskite optoelectronic devices. 28,29 As an emerging TMDs material, PtSe 2 exhibits excellent optical, electrical, stabilized and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%